2013
DOI: 10.1074/jbc.r112.446526
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Urease Metallocenter

Abstract: Metalloenzymes often require elaborate metallocenter assembly systems to create functional active sites. The medically important dinuclear nickel enzyme urease provides an excellent model for studying metallocenter assembly. Nickel is inserted into the urease active site in a GTP-dependent process with the assistance of UreD/UreH, UreE, UreF, and UreG. These accessory proteins orchestrate apoprotein activation by delivering the appropriate metal, facilitating protein conformational changes, and possibly provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
106
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 87 publications
(129 reference statements)
1
106
0
Order By: Relevance
“…In addition, a multiple-sequence alignment of BpUreC with other UreC proteins, including the iron-containing HmUreC2 (Fig. 1B), confirmed that all the amino acids involved in nickel binding (His137, His139, Lys220, His247, His275, and Asp363) and catalysis (His222 and His323) are highly conserved (3,4,31,32). The Gly280, Cys322, Arg339, and Ala366 residues, which are thought to be important for the catalytic mechanism, but not for metal binding, are also strictly conserved (32).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…In addition, a multiple-sequence alignment of BpUreC with other UreC proteins, including the iron-containing HmUreC2 (Fig. 1B), confirmed that all the amino acids involved in nickel binding (His137, His139, Lys220, His247, His275, and Asp363) and catalysis (His222 and His323) are highly conserved (3,4,31,32). The Gly280, Cys322, Arg339, and Ala366 residues, which are thought to be important for the catalytic mechanism, but not for metal binding, are also strictly conserved (32).…”
Section: Resultsmentioning
confidence: 85%
“…UreE, a metallochaperone, delivers nickel to urease apoprotein via the chaperone complex (UreD-UreF-UreG) 3 , in which UreD functions as a scaffold for the recruitment of other accessory subunits, UreF guarantees metallocenter fidelity, and UreG is a GTPase for the incorporation of nickel ions (3,4,(19)(20)(21). Although the ureD gene in Helicobacter species (18) was renamed ureH, its function is consistent with that of other UreD accessory proteins.…”
mentioning
confidence: 97%
See 3 more Smart Citations